Complete biosynthetic pathways of ascofuranone and ascochlorin in Acremonium egyptiacum - Araki, Yasuko (Proc Natl Acad Sci U S A, 2019)
Ascofuranone (AF) and ascochlorin (AC) are meroterpenoids produced by various filamentous fungi, including Acremonium egyptiacum (synonym: Acremonium sclerotigenum), and exhibit diverse physiological activities. In particular, AF is a promising drug candidate against African trypanosomiasis and a potential anticancer lead compound. These compounds are supposedly biosynthesized through farnesylation of orsellinic acid, but the details have not been established. In this study, we present all of the reactions and responsible genes for AF and AC biosyntheses in A. egyptiacum, identified by heterologous expression, in vitro reconstruction, and gene deletion experiments with the aid of a genome-wide differential expression analysis. Both pathways share the common precursor, ilicicolin A epoxide, which is processed by the membrane-bound terpene cyclase (TPC) AscF in AC biosynthesis. AF biosynthesis branches from the precursor by hydroxylation at C-16 by the P450 monooxygenase AscH, followed by cyclization by a membrane-bound TPC AscI. All genes required for AC biosynthesis (ascABCDEFG) and a transcriptional factor (ascR) form a functional gene cluster, whereas those involved in the late steps of AF biosynthesis (ascHIJ) are present in another distantly located cluster. AF is therefore a rare example of fungal secondary metabolites requiring multilocus biosynthetic clusters, which are likely to be controlled by the single regulator, AscR. Finally, we achieved the selective production of AF in A. egyptiacum by genetically blocking the AC biosynthetic pathway; further manipulation of the strain will lead to the cost-effective mass production required for the clinical use of AF.